Measuring VOC emissions from wood-based building products under real room conditions in idealised model rooms. (November 2014) - Höllbacher, E.; Rieder-Gradinger, C.; Stratev, D.; Srebotnik, E.
<x content-type="archive" xml:space="preserve">Abstract</x> Two model rooms were constructed out of OSB and CLT and applied as a large scale test method for emissions of volatile organic compounds (VOC) from wood based building products over a period of 23 weeks. The measured VOC emissions show terpene and aldehyde emissions in both model rooms. Emissions from all identified substances declined over time to a low value. In the CLT model room terpene emissions exceeded aldehyde emissions. Terpenes declined from 65 to 11 μg m−3 (83%), whereas aldehydes declined from 28 to 5 μg m−3 (82%). In the OSB model room aldehyde emissions were higher and declined from 247 to 51 μg m−3 (79%). Terpene emissions decreased from 59 to 23 μg m−3 (61%).